TRANSAKSI PEMBELIAN EMAS NON RIIL DI PT. PEGADAIAN SYARIAH KCP.DARUSSALAM DALAM PERSPEKTIF AKAD BA’I AL-MUQAYYAD (Studi Tentang Cicilan Emas Dan Konsekuensinya Pada Tabungan Emas) - Seroja, Seroja; Iqbal, Muhammad (Universitas Islam Negeri Ar-Raniry, 2020)
Gold Savings Products of PT. This Sharia pawnshop uses a gold buy and deposit system, Gold sold by the pawnshop is a non-real form of gold, so when buying gold the customer does not immediately get the gold, in this case the customer only sees the value of savings through the account balance on the gold savings account, while gold only known in the form of its value because the physical gold has not been handed over until the price is paid in full and the gold is deposited at PT. Sharia Pawnshop. Based on the description of the background of the problem above, the formulation of the problem that the writer took is: How to Determine the price, the cost of safekeeping and transaction costs on buying and selling gold non-cash at PT. KCP Darussalam Sharia Pawnshop? What are the consequences for the parties in a conditional gold purchase transaction? and How is the validity of buying and selling gold in gold savings products at PT. Pegadaian Syariah KCP Darussalam in the perspective of the contract of Ba'i al-muqayyad ?. To answer this problem, the research method used is a qualitative method that focuses on collecting documentation data, to perfect the documentation data the author also requires interview data. After conducting an in-depth analysis of the focus of the research the author can conclude. Seen from the perspective of the contract of al-muqayyad, buying and selling gold in gold savings products at PT. The KCP Darussalam Sharia Pawnshop is formally valid, because buying and selling is tied to certain conditions such as safekeeping according to Islamic law, in the Hanafiyah school of thought the requirements are those that are in line with the purpose of the transaction. Sasabah gold savings cannot take the gold before the gold installments are sufficient, then the gold must be deposited with the Islamic Pawnshop. However, in essence no gold is stored in all PT. Sharia pawnshop where customers make transactions, if customers want to take gold, gold must be ordered to PT. Antam first ± for a week, then customers are charged a maintenance fee of Rp. 30,000 per year for gold custody that was not actually carried out by PT. Sharia Pawnshop.